Kinetic Modeling Of A Bi-Enzyme Time-Temperature Indicator (TTI) Based on Different Parameters for Monitoring Food Product Quality. (October 2019) - Li, Qiang; Duan, Min; Liu, Wen; Dai, Yue; Li, Ren
Abstract: Time-temperature indicator has been widely applied in the food industry. And, the theoretical study shows that if the time-temperature indicator is applied to monitor food, the activation energy of TTI temperature-dependent must be consistent with the activation energy of food quality loss. In this study, kinetics of absorbance and color changes in bi-enzyme were investigated as a function of storage temperature. Absorbance value was used to evaluate the enzyme reaction process under different temperature. Color change was evaluated in terms of the total color difference (DE). The results indicated that the time - temperature dependence of Absorbance and DE values followed a zero-order model. The Arrhenius equation adequately described the temperature dependence of the reaction rate constants for both absorbance and color parameters, respectively, from which the activation energies and rate constant at different temperature were obtained. There were significant linear correlations between absorbance, color and time parameter.